Cluster analysis of potential autonomous vehicle (AV) adopters in Indonesia’s new capital - Eko Agus Prasetio; Dita Novizayanti; Aghnia Nadhira Aliya Putri (Transportation Research Interdisciplinary Perspectives)
Indonesia’s major cities suffer from severe traffic congestion, leading to air pollution, wasted time, higher casualty rates, reduced productivity, respiratory issues, and contributions to global warming. Autonomous Vehicles (AVs) could offer a solution by optimizing routes and enhanced efficiency, thereby reducing stop-and-go behavior that leads to congestion and lowering risks associated with current mobility options. However, uncertainties about AV safety and security remain, shaped by cultural, educational, and personal contexts. This research aims to identify strategies to boost AV adoption in Indonesia by categorizing market segments using cluster analysis, focusing on civil servants relocating to Nusantara, the new capital, where AV will be implemented earlier than other regions in the country. A survey addressing 13 factors relevant to AV adoption was distributed to 356 participants. The analysis identified four clusters: Cluster 1 (27%) values sustainability, emotional safety, and performance expectancy but needs more trust and safety assurances. Cluster 2 (16%) prioritizes perceived enjoyment, emotional safety, and sustainability, with minimal influence from mass media and social media. Cluster 3 (38%) focuses on emotional safety, perceived usefulness, and sustainability, with little impact from mass media and social media. Cluster 4 (18%) values emotional safety, perceived enjoyment, and usefulness, with the least influence from mass media, social media, and hedonic motivation. Based on this clustering, we suggest staging strategies focusing on building trust and safety, enhancing positive perceptions through targeted marketing, leveraging social influence to broaden adoption, and sustaining enthusiasm with simplified approaches and incentives. Each stage addresses specific barriers and motivations to drive AV adoption effectively.